2000
DOI: 10.1046/j.1440-1622.2000.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Laser Discectomy

Abstract: Given the extremely low level of evidence available for this procedure it was recommended that the procedure be regarded as experimental until results are available from a controlled clinical trial, ideally with random allocation to an intervention and control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Postoperatively, the scar tissue usually formed in the dorsal route after an open discectomy, and a PETD was selected if feasible. 18,[24][25][26][27] The surgical technique was similar to that in previous reports, except for general anesthesia and intraoperative electromyographic monitoring. 11,15,17 Generally, a PETD is possible at all spinal levels except for L5-S1 in patients with high iliac crests.…”
Section: Surgical Decision and Techniquementioning
confidence: 89%
See 1 more Smart Citation
“…Postoperatively, the scar tissue usually formed in the dorsal route after an open discectomy, and a PETD was selected if feasible. 18,[24][25][26][27] The surgical technique was similar to that in previous reports, except for general anesthesia and intraoperative electromyographic monitoring. 11,15,17 Generally, a PETD is possible at all spinal levels except for L5-S1 in patients with high iliac crests.…”
Section: Surgical Decision and Techniquementioning
confidence: 89%
“…15 Hoogland et al 11 reported that the rerecurrence rate was 4.6% (11/238) during a 2-year followup after a PETD. 18,[24][25][26][27] The experience of open discectomy can be utilized with PEID. 15 PED may be a good alternative for recurrent disk herniation, but we need to know how to apply the endoscopic technique effectively.…”
Section: Endoscopic Discectomy For Recurrent Disk Herniationmentioning
confidence: 99%
“…Treatment modalities include conservative measures with physiotherapy, rehabilitation, weight control, anti-inflammatory measures, epidural steroid injections, analgesia-assisted traction therapy (IVSAAT), lumbo-sacral back support and stem cell therapy 17252627282930313233343536. Surgical measures include discectomy/microdiscectomy, fenestration, laminectomy with or without discectomy, artificial disc replacement and nucleoplasty 13738394041424344. The outcome of treatment depends on the location of the prolapse, clinical condition of the patient and time of presentation and treatment 45.…”
Section: Introductionmentioning
confidence: 99%
“…These include lumbar chymopapain chemonucleolysis (LCC) [9], automated percutaneous lumbar discectomy (APLD), percutaneous laser lumbar discectomy (PLLD) [10], intradiscal electrothermal annuloplasty (IDET), microendoscopic discectomy (MED) [11] and more recently, minimally invasive nuclear decompression-known as nucleoplasty.…”
Section: Introductionmentioning
confidence: 99%